An Investigation of The Judge's Ruling on Divorce Due to Apostasy at The Religious Court of South Jakarta, Class IA (Maslahat Perspective) - Farid Mar’ie Muhammad; Sabri Samin; Hamsir Hamsir (International Journal of Islamic Studies, 2023)
The main problem of this study is an investigation of the judge's ruling on divorce due to apostasy at the religious court of South Jakarta, class IA (maslahat perspective). This study used qualitative research obtained through field research with a juridical approach. The data sources in this study were judges and clerks at the religious court in South Jakarta. Data collection was carried out through observation, interviews, and documentation methods. Meanwhile, technique processing and analysis of the data were carried out in three stages, namely data reduction, data processing, data presentation, and drawing conclusions. This study showed that: 1) The decision of the judge at the religious court in South Jakarta about the revocation of the marriage of the parties with the excuse of apostasy can be understood as the result of the petitioner, who is apostate. So that he was no longer able to create a sakinah mawaddah wa rahmah family. This has to be done to provide legal certainty and benefits for those who adhere to the Islamic religion. 2) The judge's legal consideration mentioned that the divorce has met the requirements for a good reason. 3) Legal consequences of the judge's ruling on divorce based on the reasons for Article 116 in Compilation of Islamic Law (KHI) points (a) to (g) and based on the reasons for divorce, Article 19 of the Government Regulation of the Republic of Indonesia Number 9 of 1975 about the implementation of Law of the Republic of Indonesia Number 1 of 1974 about marriage. It states that a true divorce will only result in the legal consequences of the extinguished joint property, the husband's rights, the obligation to live together, and parental rights; then it will result in the right of guardianship.